Intervensi Pembeli Terhadap Labelisasi Halal dan Kualitas Produk: Literature Review - Agus Suyatno; Karina Sukardi; Siske Tontong; Irma Hakim; Asdi Asdi (Journal of Economic, Bussines and Accounting (COSTING), 2023)
Purchasing is the stage in the purchasing decision-making process where a consumer actually buys a product. Purchasing decisions are basically a process for consumers to determine the product or service to be purchased. The decision to purchase a product is not only influenced by product quality, but also influenced by the product's halal labeling. The purpose of this article is to analyze by reference the effect of labeling and product quality on consumer purchasing decisions. The research method is in the form of literature study by reviewing various related studies recorded in Mendeley's references and Google Schoolars. All ideas from each study provide information about the methodologically desirable theory of the study being analyzed. The results of this study were analyzed and used as material for discussion to determine the answers to the problems. The results explain that there is a positive significant influence on the halal labeling of products on consumer purchasing decisions, and there is a significant influence on product quality on purchasing decisions made by consumers on goods or services. Keywords: Product Quality, Halal Labeling, Purchase Decision, Literature Review